Classical Sweet's syndrome - Saurabh R Jindal; Mahendra M Kura (Wolters Kluwer Medknow Publications, 2014)
A 38-year - old female came to us with sudden eruptions of painful edematous lesions which appeared pseudovesicular on cutaneous examination. Histopathology supported the diagnosis of sweet's syndrome and she responded to a combination of dapsone and oral steroids, after having relapsed on self-discontinuation of monotherapy with dapsone.